2021
DOI: 10.3389/fcell.2021.625540
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 Maintains Redox Homeostasis to Promote Porcine Oocyte Maturation

Abstract: SIRT6, the sixth member of the sirtuin family proteins, has been characterized as a crucial regulator in multiple molecular pathways related to aging, including genome stability, DNA damage repair, telomere maintenance, and inflammation. However, the exact roles of SIRT6 during female germ cell development have not yet been fully determined. Here, we assessed the acquisition of meiotic competency of porcine oocytes by inhibition of SIRT6 activity. We observed that SIRT6 inhibition led to the oocyte meiotic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Consistent with the fact that ROS in pig oocytes are mainly produced in the mitochondria and trigger damage to the latter [ 19 , 36 ], SDF1-mediated reduction in ROS levels of pig oocytes enhanced the mitochondrial activity of oocytes by increasing the mitochondrial membrane potential. High ROS levels also activate the apoptosis pathways in porcine oocytes [ 37 , 38 , 39 ]. In the present study, we found that SDF1 downregulated the mRNA level of the pro-apoptotic gene BAX , and upregulated the mRNA level of the anti-apoptotic genes BCL2 and GPX4 in the treated pig oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the fact that ROS in pig oocytes are mainly produced in the mitochondria and trigger damage to the latter [ 19 , 36 ], SDF1-mediated reduction in ROS levels of pig oocytes enhanced the mitochondrial activity of oocytes by increasing the mitochondrial membrane potential. High ROS levels also activate the apoptosis pathways in porcine oocytes [ 37 , 38 , 39 ]. In the present study, we found that SDF1 downregulated the mRNA level of the pro-apoptotic gene BAX , and upregulated the mRNA level of the anti-apoptotic genes BCL2 and GPX4 in the treated pig oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Such difference might be due to the fact that male germ cells did not enter the meiotic process until puberty, but our samples were derived from the 1/2 embryonic stage (before meiosis). Furthermore, the imbalance between OXPHOS and spermatogonia glycolysis could lead to meiosis failure ( Li Y, et al, 2021 ), which suggested that amino acid metabolism disturbance induced by mitochondrial oxidative phosphorylation might be reason for meiosis failure in male Mule ducks, further resulting in male Mule duck sterility ( Figure 7 ). It should be noted that merely a few amino acid metabolism pathways were enriched by DEGs in inter-breed female comparison in this study ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of SIRT2 and SIRT6 related to the protection of oocytes against aging seems to be interesting, from our point of view. Downregulation of SIRT2 and SIRT6 causes cellular fragmentation, spindle defects, elevated reactive oxygen species (ROS) accumulation, mitochondrial dysfunction, and the upregulation of autophagy [ 58 , 62 ]. In our study, the increased expression of SIRT2 and SIRT6 in the mature egg coat of oocytes just before ovulation suggests their important function in the quality control of bird oocytes before fertilization.…”
Section: Discussionmentioning
confidence: 99%